Characterization of organizational and technological conditions in the content of Aberdeen-Angus meat cows in the stall period without use of premises - Колісник, О. І.; Прудніков, В. Г.; Криворучко, Ю. І.; Нагорний, С. А. (Scientific Progress & Innovations, 2018)
The organizational and technological conditions were assessed and the meat cows and Aberdeen-Angus breeds were kept in the stall period at open feeding grounds without using capital facilities in the Eastern Region of Ukraine. The article contains a technological map of the contents of cows and heifers - the amount of work, machines and mechanisms that are used in servicing animals, labor costs, and the number of attendants. The calculations of the most labor-intensive elements are made with the content of cows and heifers in the stall period in conditions of energy-saving technology of beef cattle breeding.